Blank(et) Spaces: Weaving a Transfeminist Geography of Precarity in Academia - Acetino, Francesca; Autiero, Annachiara; Bergesio, Noemi; Bonato, Michela; Brollo, Barbara; Colla, Francesca; Eccher, Laura; Ferrante, Giulia; Garozzo, Erika; Loi, Martina; Mingo, Roberta; Pepa, Mariasole; et al. (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
The paper presents a collective autoethnography of fourteen transfeminist scholars from diverse geographical backgrounds, exploring the experience of precarity within the Italian academic landscape. We have developed a supportive network, a virtual space where we could share our struggles in the competitive and isolating neoliberal academic system, away from its toxicity that often leaves us exhausted and burdened. Responding to the call from the transfeminist journal Lüvo for contributions on feminist and decolonial geographies, we engaged in a reflexive process that led us to imagine ourselves as islands within an archipelago, ultimately transforming into a patchwork blanket that is a metaphor for our solidarity and interconnectedness. We examine themes of loneliness, anxiety, and hypermobility, revealing how these experiences intersect with gender dynamics and academic hierarchies. Our work is about care and community, as we wove together our stories to challenge the neoliberal structures of academia. Through this collective work, we aim to illuminate the complexities of our experiences and foster alliances. We hope that others will join us in our struggle.